Digital landscape mapping as an element of geoinformational support of the Braslavskie Ozyora National Park - Hahina, Natallia V.; Kurlovich, Dzmitry M.; Sipach, Viachaslau A. (Journal of the Belarusian State University. Geography and Geology, 2023)
Geoinformation support of national parks includes a set of measures aimed at collecting, accumulating, transferring, storing, protecting, processing, searching, transforming information and providing it to consumers to fulfill their functional duties. The integrated automated reference system of the Berezinsky Biosphere Reserve and national parks of Belarus was created to improve the efficiency of managing the activities of specially protected natural areas, including solving problems of preserving landscape and biological diversity. This system combines into an information and reference structure such processes as the collection of field information, its storage, processing and visualisation for various services in the form of web maps and web applications, work with tabular data, various archival and new cartographic materials, remote sensing data Earth. The integrated automated reference system of the Braslavskie Ozyora National Park includes structural components of cartographic and information and reference and information support. Their elements are digital thematic maps, a landscape map at a scale of 1 : 100 000, and reference information obtained from their analysis. As a result of the study, a complex landscape structure of the territory of the national park was revealed, within the boundaries of which 7 genera and 21 types of landscapes were identified. It was clarified that lacustrine-glacial landscapes prevail on the territory of the national park, occupying 30.8 % of its area. As part of the reference and information support, the landscape structure of functional zones was determined. Within the boundaries of the park, the basis of strict protection of natural landscapes is flat lacustrine-glacial landscapes with hollows and hollows and lacustrine-marsh landscapes with convex raised and transitional bogs. The methods of digital landscape mapping, geoinformation and comparative analysis were used. The results obtained can be used to correct the boundaries of the functional zones of the Braslavskie Ozyora National Park and improve its geographic information system. Methodological approaches to the construction of an integrated automated reference system can also be applied to other specially protected natural areas.